Kinetics of Free-Radical Nonbranched-Chain Processes of Formation of 1,2-Alkanediols, Carbonyl Compounds, and Methanol in Alcohol–Formaldehyde Solutions Including Determination of Free Formaldehyde and Solvent Concentrations (International Journal of Innovative Research in Computer Science & Technology, 2018)
A mechanism of the initiated nonbranched-chain process of form ing 1,2-alkanediols, carbonyl compounds, and methanol in alco hol–formaldehyde systems is suggested. The quasi-steady-state  treatment is used to obtain kinetic equations that can describe the  nonmonotonic (with a maximum) dependences of the formation  rates of the products on the concentration of free unsolvated for maldehyde. The experimental concentrations of the free unsol vated form of formaldehyde are given at the different temperatures,  solvent permittivity, and total concentrations of formaldehyde in  water and alcohols. An empirical equation for calculating the free  formaldehyde concentration in alcohol–formaldehyde (including  water/ethanediol –formaldehyde) systems at various temperatures  and total formaldehyde concentrations and an equation for eva luating solvent concentrations in these systems were derived. The  experimental dependence of the ethanediol radiation-chemical  yields on formaldehyde concentration in γ-radiolysis of metha nol–formaldehyde system at 373–473 K is shown.
Keywords: nonbranched-chain process; free formaldehyde; 1-hydroxyalkyl radical; formyl radical; competing reaction; equa tion.